Shear Fatigue Performance of Epoxy Resin Waterproof Adhesive Layer on Steel Bridge Deck Pavement - Xu, Ying; Lv, Xinpeng; Ma, Chunfeng; Liang, Fengming; Qi, Jiafei; Chou, Zhijing; Xu, Shifa (Frontiers in Materials, 2021)
In this study, the effects of temperature, shear stress, and coating quantity of waterproof adhesive layer on the shear fatigue performance of a steel bridge deck pavement were investigated. Direct shear fatigue tests of a pavement comprising an epoxy resin waterproof adhesive layer with stone matrix asphalt (SMA) were conducted at different temperatures, stress levels, and coating quantities. The results show that temperature and stress have significant effects on the shear fatigue life. With increasing temperature and stress, the shear fatigue life of the waterproof adhesive layer decreased gradually. Therefore, for steel bridge deck pavements under high temperatures and heavy loads, the use of asphalt waterproof adhesive layers or pavement layers should be evaluated carefully while limiting the traffic of heavily loaded vehicles. Shear failure occurs at the waterproof adhesive layer–pavement interface and not at the steel–waterproof adhesive layer interface. The shear strength of the epoxy resin waterproof adhesive layer is mainly provided by the bond strength between the waterproof adhesive and pavement mixture as well as the interlocking force between the cured epoxy resin and the bottom interface of uneven pavement mixture. The shear strength increases with the coating quantity of the waterproof adhesive layer; however, after reaching the maximum value, the shear strength becomes stable. In contrast, the interlaminar shear fatigue life increases continuously with the coating quantity of the waterproof adhesive layer. Appropriately increasing the coating quantity is beneficial for improving the resistance of the waterproof adhesive layer to interlaminar shear fatigue failure.